2015
DOI: 10.1016/j.joca.2014.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in subchondral bone plate, trabecular bone and articular cartilage properties of rabbit femoral condyles at 4 weeks after anterior cruciate ligament transection

Abstract: In this model of early OA, significant changes in volume and microstructure of subchondral bone plate and trabecular bone were detected only in the femoral medial condyle, while alterations in articular cartilage properties were more severe in the lateral compartment. The former finding may be associated with reduced joint loading in the medial compartment due to ACLT, while the latter finding reflects early osteoarthritic changes in the lateral compartment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
63
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 47 publications
(51 reference statements)
10
63
0
1
Order By: Relevance
“…These trends became statistically significant by week 9. Similar trends are reported in earlier studies (Bouchgua et al , 2009b; Florea et al , 2015; Pinney et al , 2012; Wang et al , 2007). Treatment with Dex did not restore bone volume fraction, but with Av-Dex, the difference in BV/TV between ACLT and control groups was no longer statistically significant (Table 3b).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These trends became statistically significant by week 9. Similar trends are reported in earlier studies (Bouchgua et al , 2009b; Florea et al , 2015; Pinney et al , 2012; Wang et al , 2007). Treatment with Dex did not restore bone volume fraction, but with Av-Dex, the difference in BV/TV between ACLT and control groups was no longer statistically significant (Table 3b).…”
Section: Resultssupporting
confidence: 91%
“…Therefore, it was not possible to assess the effect of Dex or Av-Dex on these parameters. Abnormal joint loading (due to ACLT in this model) can lead to an adaptive bone remodelling process, decreasing trabecular bone volume fraction and thickness, due to an imbalance in bone resorption and formation in the more unloaded joint compartments (Florea et al , 2015). Finally, it was found that avidin penetrated through the complete thickness of articular cartilage and was retained within the tissue until at least 3 weeks (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cartilage-onbone samples were harvested and biomechanical measurements were conducted on the medial (med) and lateral (lat) femoral condyles and tibial plateaus in the center of the weight-bearing areas and on the femoral groove in the center of the contact area with the patella for the knee in its neutrally flexed position (Julkunen et al, 2009a;Makela et al, 2014;Wei et al, 1998) (Fig. 1, see more details from Makela et al (2014) and Florea et al (2014) where the same samples were used). There were no significant differences (p 40.05) in sample thicknesses between ACLT, C-L and CTRL groups.…”
Section: Samples and Processingmentioning
confidence: 99%
“…Volumetric shapes include strips (Batiste et al, 2004), cylinders (Boudenot et al, 2014; Iijima et al, 2015; Intema et al, 2010; McErlain et al, 2008; Sniekers et al, 2008), and cubes (Florea et al, 2015). Sizes vary from small 2 x 2 x 4mm 3 cubes (Florea et al, 2015) to large anatomical contours that include the medial or lateral compartments of the tibia (Hamann et al, 2012; Maerz et al, 2016; Mohan et al, 2016). ROI location and number varies from a single load bearing location (Batiste et al, 2004; Boudenot et al, 2014) to multiple locations throughout the compartment (McErlain et al, 2008).…”
Section: Introductionmentioning
confidence: 99%